Development of a Vaccine Confidence Index for Monitoring and Assessing Parental Confidence in Childhood Vaccination. (4th October 2017) - Frew, Paula; Murden, Raphiel; Mehta, C Christina; Chamberlain, Allison; Hinman, Alan R; Nowak, Glen; Mendel, Judith; Aikin, Ann; Randall, Laura A; Hargreaves, Allison L; Omer, Saad; Orenstein, Walter A; et al.
Abstract: Background: We aimed to develop a Vaccine Confidence Index (VCI) capable of detecting variations in parental confidence toward childhood immunizations while accounting for an array of socio-ecologic factors impacting vaccine confidence. Such a VCI could be used to monitor vaccine confidence broadly or in clinical practice to assess individual parent confidence. Methods: A web-based national survey of 893 parents of children <7 years was conducted in 2016 to identify and assess items that encompassed five domains of potential correlates identified in a National Vaccine Advisory Committee report on confidence (i.e., Information Environment, Trust, Healthcare Providers, Attitudes and Beliefs, and Social Norms). Exploratory factor analysis, Cronbach's alpha, and assessments of coefficient of variation were used to identify subscale elements and create a parsimonious VCI that correlated with vaccine uptake. . Summary scores were stratified into a four-level categorical confidence variable that was assessed against self-reported childhood vaccine receipt using the Cochran-Armitage test for trend. Results: From the original 29 variables, we created an 8-item VCI with scores that could range from 0–24 (alpha = 0.857); higher scores indicate greater confidence in vaccines and vaccination systems. In this sample of parents, the mean VCI was 17.5 (SD 4.8). Higher VCI category was significantly associated with higher reported vaccine coverage (P < 0.0022 for all comparisons using Cochran-Armitage test for trend). Across nine vaccines, self-reported coverage in the lowest VCI category ranged 53%-77%, compared with 88%-98% in the highest VCI category. Coverage patterns across VCI levels were similar for all vaccines. Conclusion: We developed an efficient and reliable VCI that can be used to measure parental attitudes and perceptions while being sensitive to a number of issues that may influence vaccine confidence. The VCI will be useful for measuring parents' confidence in recommended childhood vaccinations at broad (e.g., nationally or in a community) or individual levels (e.g., a physicians' office) as well as over time. Disclosures: All authors: No reported disclosures.